Liquid-based cytology by DNA-Citoliq system (DCS) – efficacy in identification of vaginal microbiota - Alves, Venâncio A.F.; Castelo Filho, Adauto; Namiyama, Gislene; Longatto Filho, Adhemar; Vianna, Maria Regina; Taromaru, Eliane; Dôres, Gerson Botacini das (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: DNA-Citoliq System® (DCS) (Digene, Brasil) is a new liquid based cytology system for cervical material intended both for oncologiccytology and molecular tests for HPV, Neisseria gonorrhoea, and Chlamydia trachomatis. Recent studies have shown its high sensitivity for identif-ying epithelial lesions. Objective: compare the efficacy between specimens prepared with DCS and conventional Pap for morphological infectiousagent’s diagnosis. Methods: samples were collected from 3,129 women. After cervical scraping with Ayre spatula and endocervical brushing, thesample was immediately smeared on the slides and alcohol-fixed. The same brush with residual endocervical cells was again used to scrape the ecto-cervical surface and placed in a tube with Universal Collection Medium (UCM) and processed at the laboratory according to DCS protocol. All slideswere stained by the conventional Papanicolaou method. Results: both methods yielded equal results for lactobacilli (p=0.32), cocci (p=0.98), Actinomyces sp (p=1.0), Leptotrix vaginalis (p=0.37), Chlamydia trachomatis (p=0.45) and Candida sp(p=0.75). Gardnerella vagnalis (p=0.0001) was seen significantly more on DCS slides, whereas Trichomonas vaginalis was more frequently seen on the conventional slides (p=0.001). Conclusion: besides yielding high sensitivity for detecting squamous lesions and proving to be suitable for molecular tests as reported in other studies, DNA Citoliq performed as well as conventional smear in the identification of microbiological agents.